2010
DOI: 10.1139/y10-049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium houttuyfonate on inhibiting ventricular remodeling induced by abdominal aortic banding in rats

Abstract: Ventricular remodeling is an independent risk factor for many cardiovascular events. Inhibiting ventricular remodeling early may be an effective way to postpone heart failure for patients with cardiovascular illness. The study was designed to examine the effect of sodium houttuyfonate on ventricular remodeling induced by pressure overload in rats, as well as to explore the mechanisms involved. The model rats in which ventricular remodeling was induced abdominal aortic banding (AAB) were randomly divided into 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…From the findings mentioned above, we speculated that increased I Na.L may partly participate in the pathogenesis of myocardial hypertrophy and ventricular remodeling. Furthermore, experimental studies revealed that SH inhibited myocardial hypertrophy and attenuated ventricular remodeling [5,6]. Thus, the alleviative effects of myocardial hypertrophy and ventricular remodeling by SH may be related to the inhibition of increased I Na.L .…”
Section: Effects Of Sh On the Amplitude Of I Krmentioning
confidence: 99%
See 2 more Smart Citations
“…From the findings mentioned above, we speculated that increased I Na.L may partly participate in the pathogenesis of myocardial hypertrophy and ventricular remodeling. Furthermore, experimental studies revealed that SH inhibited myocardial hypertrophy and attenuated ventricular remodeling [5,6]. Thus, the alleviative effects of myocardial hypertrophy and ventricular remodeling by SH may be related to the inhibition of increased I Na.L .…”
Section: Effects Of Sh On the Amplitude Of I Krmentioning
confidence: 99%
“…f The concentration-response relationship curve for the effects of SH on I Na.P , fitted to the Hill equation. Discussion SH, a chemical compound originating from the Chinese herb Houttuynia cordata, was reported to have antibacterial and antifungal effects, as well as cardioprotective effects [1][2][3][4][5][6]. However, the effects of SH on cardiac electrophysiology remain unknown.…”
Section: Effects Of Sh On the Amplitude Of I Krmentioning
confidence: 99%
See 1 more Smart Citation
“…Houttuynia cordata Thunb (Saururaceae family) is an edible plant used in traditional Chinese medicine for the treatment of a wide range of infectious diseases, including pneumonia (Gao et al, 2009, 2010; Li et al, 2014). The major constituent of the volatile oil derived from H. cordata , sodium houttuyfonate [SH, CH 3 (CH 2 ) 8 COCH 2 CHOHSO 3 Na] is a product of the addition reaction of sodium bisulfite and houttuynin [i.e., decanoyl acetaldehyde, CH 3 (CH 2 ) 8 COCH 2 CHO] (Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The major constituent of the volatile oil derived from H. cordata , sodium houttuyfonate [SH, CH 3 (CH 2 ) 8 COCH 2 CHOHSO 3 Na] is a product of the addition reaction of sodium bisulfite and houttuynin [i.e., decanoyl acetaldehyde, CH 3 (CH 2 ) 8 COCH 2 CHO] (Wang et al, 2002). SH is the active compound of the Houttuynia plant, the healing properties of which have been recorded in ancient Chinese medical writings (Gao et al, 2010). SH is mainly used for treating purulent skin infections, respiratory tract infections, including pneumonia in elderly patients, and chronic bronchitis (Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%